Anxiety- and Depressive-Like Behaviors are Associated with Altered Hippocampal Energy and Inflammatory Status in a Mouse Model of Crohn's Disease. (16th December 2017) - Haj-Mirzaian, Arya; Amiri, Shayan; Amini-Khoei, Hossein; Hosseini, Mir-Jamal; Haj-Mirzaian, Arvin; Momeny, Majid; Rahimi-Balaei, Maryam; Dehpour, Ahmad Reza
Graphical abstract: Highlights: DNBS induced colitis and inflammatory responses in the mice. Colonic inflammatory responses were associated with hippocampal upregulation of TLRs. These inflammatory responses were associated with behavioral abnormalities in mice. Oxidative stress and innate immunity may play a role in psychiatric comorbidities in colitis. Abstract: Depression and anxiety are common comorbid disorders observed in patients with inflammatory bowel disease (IBD). Increasing line of evidence indicates that immune-inflammatory responses are involved in co-occurrence of mood disorders and IBD. However, the mechanisms through which immune-inflammatory pathways modulate this comorbidity are not yet understood. This study investigated the role of innate immunity in the development of behavioral abnormalities associated with an animal model of Crohn's disease (CD). To do this, we induced colitis in male adult mice by intrarectal (i.r.) injection of DNBS (Dinitrobenzene sulfonic acid). After 3 days, we performed behavioral tests for anxiety- and depressive-like behaviors as well as tissue collection. Our results showed that DNBS-induced colonic inflammatory responses were accompanied by infiltration of inflammatory cells, and increased expression of genes involved in toll-like receptor signaling pathway in intestinal tissue. Furthermore, the DNBS-treated mice showed depressive- and anxiety-like behaviors which were associated with increased expression of the inflammatory genes and abnormal mitochondrial function in the hippocampus. These results suggest that peripheral inflammation is able to increase the transcriptional level of the genes in toll-like receptor pathway, induces abnormal mitochondrial function in the hippocampus, and these negative effects may be involved in the co-occurrence of anxiety and depression in early stages of CD.